Increased CD69+CCR7+ circulating activated T cells and STAT3 expression in cutaneous lupus erythematosus patients recalcitrant to antimalarials. (April 2022) - Zeidi, Majid; Chen, Kristen L; Patel, Jay; Desai, Krisha; Kim, Hee Joo; Chakka, Srita; Lim, Rachel; Werth, Victoria P
Background: Antimalarials are first-line systemic therapy for cutaneous lupus erythematosus (CLE). While some patients unresponsive to hydroxychloroquine (HCQ) alone benefit from the addition of quinacrine (QC), a subset of patients is refractory to both antimalarials. Methods: We classified CLE patients as HCQ-responders, HCQ+QC-responders, or HCQ+QC-nonresponders to compare immune profiles. Immunohistochemistry, immunofluorescence, and qRT-PCR were used to characterize inflammatory cells and cytokines in lesional skin. Results: Immunohistochemistry showed that CD69 + T cells were higher in HCQ+QC-nonresponders compared to HCQ- and HCQ+QC-responders ( p < 0.05). Immunofluorescence further identified these cells as CD69+CCR7+ circulating activated T cells. Myeloid dendritic cells were significantly higher in HCQ+QC-responders compared to both HCQ-responders and HCQ+QC-nonresponders. Plasmacytoid dendritic cells were significantly increased in HCQ-responders compared to HCQ- and HCQ+QC-nonresponders. No differences were found in the number of autoreactive T cells, MAC387+ cells, and neutrophils among the groups. CLASI scores of the HCQ+QC-nonresponder group positively correlated with CD69+CCR7+ circulating activated T cells (r = 0.6335, p < 0.05) and MAC387+ cells (r = 0.5726, p < 0.05). IL-17 protein expression was higher in HCQ+QC-responders compared to HCQ-responders or HCQ+QC-nonresponders, while IL-22 protein expression did not differ. mRNA expression demonstrated increased STAT3 expression in a subset of HCQ+QC-nonresponders. Conclusion: An increased number of CD69+CCR7+ circulating activated T cells and a strong correlation with CLASI scores in the HCQ+QC-nonresponders suggest these cells are involved in antimalarial-refractory skin disease. STAT3 is also increased in HCQ+QC-nonresponders and may also be a potential target for antimalarial-refractory skin disease.